Electro-optic control of the external coupling strength of a high-quality-factor lithium niobate micro-resonator - Hwang, Hyeon; Heo, Hyungjun; Ko, Kiyoung; Nurrahman, Mohamad Reza; Moon, Kiwon; Ju, Jung Jin; Han, Sang-Wook; Jung, Hojoong; Lee, Hansuek; Seo, Min-Kyo (Optical Society of America, 2022)
Controlling the optical coupling between a micro-resonator and waveguide plays a key role in on-chip photonic circuits. Here, we demonstrate a two-point coupled lithium niobate (LN) racetrack micro-resonator that enables us to electro-optically traverse a full set of the zero-, under-, critical-, and over-coupling regimes with minimized disturbance of the intrinsic properties of the resonant mode. The modulation between the zero- and critical-coupling conditions cost a resonant frequency shift of only similar to 344.2MHz and rarely changed the intrinsic quality (Q) factor of 4.6x10(5). Our device is a promising element in on-chip coherent photon storage/retrieval and its applications. (c) 2022 Optica Publishing Group